2021
DOI: 10.1038/s41598-021-87037-w
|View full text |Cite
|
Sign up to set email alerts
|

Mining the plasma-proteome associated genes in patients with gastro-esophageal cancers for biomarker discovery

Abstract: Gastro-esophageal (GE) cancers are one of the major causes of cancer-related death in the world. There is a need for novel biomarkers in the management of GE cancers, to yield predictive response to the available therapies. Our study aims to identify leading genes that are differentially regulated in patients with these cancers. We explored the expression data for those genes whose protein products can be detected in the plasma using the Cancer Genome Atlas to identify leading genes that are differentially reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Comparison between normal stomach tissue and stomach tumors showed the leading five genes that were overexpressed in stomach cancer. According to their analysis, ACAN gene showed significant upregulation in all stages of cancer (Vizeacoumar et al, 2021). Similar research was performed to investigate the interaction of miRNAs and target genes in Stomach adenocarcinoma (STAD).…”
Section: Discussionmentioning
confidence: 93%
“…Comparison between normal stomach tissue and stomach tumors showed the leading five genes that were overexpressed in stomach cancer. According to their analysis, ACAN gene showed significant upregulation in all stages of cancer (Vizeacoumar et al, 2021). Similar research was performed to investigate the interaction of miRNAs and target genes in Stomach adenocarcinoma (STAD).…”
Section: Discussionmentioning
confidence: 93%
“…Co-expression network analysis processed pDEGs for identification of gene-signature. Details of procedure can be accessed from doi.org/10.1038/s41598-021-87037-w [36]. Gene-wise similarity correlation matrix (scor) & dis-similarity correlation matrix (dcor) presented co-expression of pDEGs.…”
Section: Genotype For Earlydetectmentioning
confidence: 99%
“…Saini et al [ 122 ] report detection of MMRN1 in the saliva of epithelial ovarian cancer patients but comment that the route by which MMRN1 enters the saliva remains unclear. Vizecoumar et al [ 177 ] identified MMRN1 as a downregulated gene whose protein product is detectable in the plasma in gastro-oesophageal cancer patients. Using mass spectrometry techniques, changes in MMRN1 protein levels were detected in the sera of multiple myeloma patients [ 178 ] and hepatocellular carcinoma patients [ 116 ] and in cell lysates from bone marrow aspirates from patients with amyloid leukaemia [ 179 ].…”
Section: Mmrn1 Protein Detection In Cancermentioning
confidence: 99%